The effect of the financial crisis on macroeconomic variables in Iraq, Iran, and Turkey - Younis Ali Ahmed; Biaban Nwri Rostam; Burhan Ali Mohammed (Economic Journal of Emerging Markets, 2020)
This study investigates the effect of financial crises on macroeconomic variables that include gross domestic product (GDP), export, inflation, and exchange rates, in some developing countries, namely Iraq, Iran, and Turkey, from 1980 to 2017. In doing so, it performed unit root and cointegration tests and employed generalized least square and panel dynamic least squares estimating methods. Findings/Originality: The empirical results show that the financial crises affect GDP, export, inflation, and exchange rates of the countries at different levels. While the Asian financial crisis shows a significant negative effect on GDP in Iran and Iraq, the global financial crisis exhibits a negative influence on export in all countries. Nevertheless, both Asian and global crises positively affect inflation because financial crises reduce expenditure at the family and government levels. Thus, governments worldwide attempt to minimize the inflation rate.